Recent advances in dermatology - Ghosh, Sanjay; Sarma, Nilendu; De, Dipankar (Dermatologist) (Jaypee Brothers Medical Publishers (P) Ltd., 2014)
Fully revised, new volume bringing clinicians and trainees fully up to date with the latest advances in dermatology, with emphasis on etiology, clinical features, diagnosis and treatment. Previous volume published in 2007.